Pengaruh Green Product dan Green Marketing Terhadap Keputusan Pembelian Produk the Body Shop - Nur Aini Iftinia Aprilia; Diah Widiawati; Sunaryati Hardiani (Business Management Research, 2023)
The purpose of this study is to examine how the influence of green products influences purchasing decisions, how the influence of green marketing influences purchasing decisions, the simultaneous influence of green products and green marketing on purchasing decisions, and which of the green products and green marketing has a greater influence on purchasing decisions using a sample of 100 people. Respondents were drawn from the female population of Malang who had purchased items from The Body Shop. Random sampling technique is used for sampling. Multiple linear regression analysis is used in data analysis to test hypotheses and produce green product has a positive and significant impact on purchasing decisions, green marketing has a positive and significant impact on purchasing decisions, green product and green marketing both have a positive and significant impact on purchasing decisions, green product and green marketing both have a positive and significant impact on purchasing decisions, and green marketing has a dominant influence on purchasing decisions.